Preparation method and application of corrosion-resistant micro-arc oxidation film layer
By introducing bipolar ultra-audio pulse technology in the microarc oxidation process, optimizing the microarc oxidation parameters, the problems of large porosity and rough surface of conventional microarc oxidation films are solved, and high corrosion resistance and adjustable film thickness are achieved. microarc oxide film layer.
Patent Information
- Application Number
- CN202411512904.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The membrane layer obtained by conventional microarc oxidation process has a large porosity and has large micropores and microcracks, resulting in uneven and rough surface of the membrane layer, affecting the performance of the membrane layer.
Bipolar ultra-audio pulse microarc oxidation system is used, and the microarc oxidation parameters are set to voltage -50~600V, pulse frequency 1kHz~150kHz, duty cycle 0.1~0.5, and microarc oxidation of preset time is carried out to form corrosion-resistant micro Arc oxide film layer.
Through ultra-audio pulse technology, the number of arc starting points is increased, the amount of molten oxide generation during breakdown discharge is reduced, the submicron-scale pore structure is obtained, the film layer is roughened, and the two-dimensional communication and film layer thickness are achieved through negative pulse voltage. Adjustable to obtain a high corrosion resistance microarc oxide film layer.
Smart Images

Figure CN119392331A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface modification, and in particular to a preparation method and application of a corrosion-resistant micro-arc oxidation film. Background Art
[0002] Valve metals such as aluminum, magnesium, and titanium and their alloys are lightweight, high-strength materials that are widely used in aerospace, rail transportation, automobile manufacturing, electronic products, and other fields. However, the corrosion and wear resistance of the aluminum-magnesium-titanium alloy surface is poor. Therefore, in order to improve the wear and corrosion resistance of aluminum-magnesium-titanium and other alloy materials, it is necessary to modify the surface of the metal to ensure that aluminum-magnesium-titanium and other alloys can be used in some special fields and have a long service life.
[0003] At present, the widely used surface modification methods mainly include ion implantation, anodizing, laser surface treatment, electroplating, chemical plating and other methods. Among them, micro-arc oxidation technology is a surface modification technology for in-situ growth of ceramic layers on the surface of valve metals (Al, Mg, Ti, etc.) and their alloys. It uses spark discharge to generate ceramic layers on the alloy surface. It has strong bonding with the substrate and has excellent corrosion resistance, wear resistance, thermal shock resistance and other excellent properties. It has the advantages of simple process, high efficiency and no pollution, and has gradually become a commonly used surface treatment method for valve metals and their alloys. However, the film layer obtained by conventional micro-arc oxidation process has a large porosity, large micropores and microcracks, and the obtained film layer has defects such as uneven surface and roughness, which greatly affects the performance of the film layer. Summary of the invention
[0004] The embodiment of the present invention provides a method for preparing a corrosion-resistant micro-arc oxidation film and an application thereof, so as to solve the problem that the film obtained by conventional micro-arc oxidation process has poor performance.
[0005] In a first aspect, an embodiment of the present invention provides a method for preparing a corrosion-resistant micro-arc oxidation film layer, comprising:
[0006] Pre-treating valve metal and / or its alloy substrate;
[0007] The pretreated valve metal and / or its alloy substrate is immersed in the electrolyte of a bipolar ultrasonic pulse micro-arc oxidation system, and the micro-arc oxidation parameters are set to a voltage of -50 to 600 V, a power output pulse frequency of 1 kHz to 150 kHz, and a duty cycle of 0.1 to 0.5. Micro-arc oxidation is performed for a preset time to obtain a metal substrate with a corrosion-resistant micro-arc oxidation film layer.
[0008] In a possible implementation, the micro-arc oxidation parameters are alternating positive pulse voltage and negative pulse voltage, the forward voltage is 300V to 500V, the negative voltage is -10V to -50V, the pulse frequency is 1kHz to 150kHz, and the duty cycle is 0.3 to 0.5.
[0009] In a possible implementation, the preset duration is 10 to 60 minutes.
[0010] In a possible implementation, the corrosion-resistant micro-arc oxidation film has a double-layer structure, wherein the inner layer is a dense layer and the outer layer has a two-dimensional interconnected porous structure.
[0011] In a possible implementation, the total thickness of the corrosion-resistant micro-arc oxidation film is 5 to 20 μm, the thickness of the inner layer is 0.5 to 3 μm, and the micropore size of the outer layer is 0.1 to 3 μm.
[0012] In a possible implementation, pre-treating the valve metal and / or its alloy substrate includes:
[0013] The valve metal and / or its alloy substrate is ground, polished, laser cleaned or etched to obtain etch pits evenly distributed on the surface of the valve metal and / or its alloy substrate.
[0014] In a possible implementation, the power of laser cleaning is 5 to 30 W, and the diameter of the etching pit is 5 to 30 μm.
[0015] In a possible implementation, the electrolyte includes 2-4 g / L alkaline agent, 10-20 g / L metal salt, 1-2 g / L chelating agent and 0.1-1 g / L complexing agent.
[0016] In a possible implementation, the alkaline agent is NaOH or KOH, the metal salt is sodium silicate, the chelating agent is citric acid or sodium fluoride, and the complexing agent is one or more of disodium ethylenediaminetetraacetate and sodium phytate.
[0017] In a second aspect, an embodiment of the present invention provides a metal product, the material of which is valve metal and / or its alloy, and the surface treatment of micro-arc oxidation is performed based on the steps of the method described in the first aspect or any possible implementation of the first aspect.
[0018] The embodiment of the present invention provides a method for preparing a corrosion-resistant micro-arc oxidation film and its application. The ultrasonic pulse is used to greatly increase the number of arc starting points in the micro-arc oxidation process and reduce the amount of molten oxide generated during breakdown discharge, so that the surface of the film layer obtains a submicron-level hole structure and reduces the roughness of the micro-arc oxidation film layer. At the same time, by coupling a negative pulse voltage, the microporous surface is ablated to achieve two-dimensional interconnection and adjustable film thickness, thereby obtaining a highly corrosion-resistant micro-arc oxidation film layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0020] Figure 1 It is a flow chart of a method for preparing a corrosion-resistant micro-arc oxidation film provided by one embodiment of the present invention;
[0021] Figure 2 is a schematic diagram of an output voltage waveform of a micro-arc oxidation process provided by an embodiment of the present invention;
[0022] Figure 3A Surface morphology of micro-arc oxidation film prepared on magnesium alloy sandpaper-polished substrate (SP) at 34 s;
[0023] Figure 3B Surface morphology of micro-arc oxidation film prepared on magnesium alloy sandpaper-polished substrate (SP) at 36 s;
[0024] Figure 3C Surface morphology of micro-arc oxidation film prepared on magnesium alloy sandpaper-polished substrate (SP) at 41 s;
[0025] Figure 3D Surface morphology of the micro-arc oxidation film prepared on the magnesium alloy sandpaper-polished substrate (SP) at 51 s;
[0026] Figure 3E Surface morphology of micro-arc oxidation film prepared for laser cleaning substrate (LC) at 34 s;
[0027] Figure 3F Surface morphology of micro-arc oxidation film prepared for laser cleaning substrate (LC) at 36 s;
[0028] Figure 3G Surface morphology of micro-arc oxidation film prepared for laser cleaning substrate (LC) at 41 s;
[0029] Figure 3H The surface morphology of the micro-arc oxidation film layer was prepared for laser cleaning of the substrate (LC) at 51 s;
[0030] Figure 4 The potentiodynamic polarization curves of SP sample and LC sample after micro-arc oxidation at different powers in 3.5% NaCl solution;
[0031] Figure 5A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 6;
[0032] Figure 5B is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Example 6;
[0033] Fig. 6A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 7;
[0034] Figure 6B is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Example 7;
[0035] Fig. 7A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 8;
[0036] Figure 7B is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Example 8;
[0037] Fig. 8A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 9;
[0038] Figure 8B is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Example 9;
[0039] Fig.9A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 10;
[0040] Fig. 9B is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Example 10;
[0041] Fig.10 Polarization curves of the micro-arc oxidation films of Examples 6 to 10 in 3.5% NaCl solution;
[0042] Fig.11 is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 11;
[0043] Fig.12 is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 12;
[0044] Fig.13 is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 13;
[0045] Fig.14 is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Comparative Example 1;
[0046] Fig.15 A scanning electron micrograph of a cross section of a micro-arc oxidation film layer of Comparative Example 2;
[0047] Fig.16 is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Comparative Example 3;
[0048] Fig.17 is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Comparative Example 4;
[0049] Fig.18 is a scanning electron micrograph of a cross section of the micro-arc oxidation film of Comparative Example 5;
[0050] Fig.19 is a scanning electron micrograph of a cross section of a micro-arc oxidation film layer of Comparative Example 6;
[0051] Fig. 20 is a scanning electron micrograph of a cross section of a micro-arc oxidation film layer of Comparative Example 7;
[0052] Fig.21 This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Comparative Example 8. DETAILED DESCRIPTION
[0053] In the following description, specific details such as specific system structures, technologies, etc. are provided for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from obstructing the description of the present invention.
[0054] In order to make the purpose, technical solutions and advantages of the present invention more clear, specific embodiments will be described below in conjunction with the accompanying drawings.
[0055] See also Figure 1 , which shows a flow chart of the method for preparing the corrosion-resistant micro-arc oxidation film provided by an embodiment of the present invention, and is described in detail as follows:
[0056] Step 101 : pretreating the valve metal and / or its alloy substrate.
[0057] In this embodiment, the method of pretreating the surface of the valve metal and / or its alloy substrate generally includes grinding, polishing, cleaning, and drying. The pretreatment can remove oil, rust, oxide layer, etc. on the surface of the workpiece, ensure that the electrolyte can be evenly in contact with the substrate metal during the micro-arc oxidation process to form a uniform oxide film, increase the roughness of the substrate metal surface, make the oxide film and the substrate more firmly bonded, remove tiny cracks, holes and other defects on the surface of the material, avoid these defects from expanding during the micro-arc oxidation process and affecting the quality of the oxide film, improve the conductivity of the metal surface, facilitate the uniform distribution of current during the micro-arc oxidation process, and promote the formation of the oxide film.
[0058] Step 102, immersing the pretreated valve metal and / or its alloy substrate into the electrolyte of a bipolar ultrasonic pulse micro-arc oxidation system, setting the micro-arc oxidation parameters to a voltage of -50 to 600 V, a power output pulse frequency of 1 kHz to 150 kHz, and a duty cycle of 0.1 to 0.5, and performing micro-arc oxidation for a preset time to obtain a metal substrate with a corrosion-resistant micro-arc oxidation film layer.
[0059] In this embodiment, the bipolar super-frequency pulse micro-arc oxidation system includes a bipolar super-frequency pulse micro-arc oxidation power supply, an oxidation system, a water cooling system and a data acquisition system. The micro-arc oxidation system includes a box, an anode, a cathode and a power supply, wherein the box contains an electrolyte, the cathode is a stainless steel plate, connected to the negative electrode of the power supply, and the anode is a valve metal and / or its alloy matrix, connected to the positive electrode of the power supply. The water cooling system includes a water pump, a chiller and a heat exchanger to control the electrolyte temperature below 30°C.
[0060] The data acquisition system includes a voltage Hall sensor, a current Hall sensor, a pH sensor, a temperature sensor and a conductivity sensor to realize the collection of electrical parameters (current, voltage, frequency, duty cycle) and electrolyte parameters (temperature, conductivity, pH value) during the micro-arc oxidation process.
[0061] Through the micro-arc oxidation parameters in this embodiment, micro-arc oxidation can be achieved using alternating positive and negative ultrasonic pulses. The introduced negative pulses provide negative charges, neutralize the excess positive charges on the surface of the film layer, and avoid the generation of destructive arc light. On the one hand, the spark discharge intensity is reduced, and on the other hand, sufficient time can be provided for the cooling of the molten oxide before the next positive pulse arrives. These are all conducive to the formation of a dense oxide film layer and the improvement of corrosion resistance, thereby obtaining a corrosion-resistant micro-arc oxidation film layer.
[0062] The embodiment of the present invention adopts ultrasonic pulses to shorten the single arcing time, increase the number of arcing per unit time, promote the growth rate of micro-arc oxidation film, improve the production efficiency of micro-arc oxidation, and can greatly increase the number of arcing points in the micro-arc oxidation process, reduce the amount of molten oxide generated during breakdown discharge, so that the surface of the film layer obtains a submicron-level hole structure, and reduces the roughness of the micro-arc oxidation film layer. At the same time, coupled with negative pulse voltage, the microporous surface is ablated to achieve two-dimensional interconnection and adjustable film thickness, thereby obtaining a highly corrosion-resistant micro-arc oxidation film layer.
[0063] In a possible implementation, the micro-arc oxidation parameters are alternating positive pulse voltage and negative pulse voltage, the forward voltage is 300V to 500V, the negative voltage is -10V to -50V, the pulse frequency is 1kHz to 150kHz, and the duty cycle is 0.3 to 0.5.
[0064] In this embodiment, the on-off timing and output voltage waveform of the chopper in the bipolar pulse voltage mode are as follows: Figure 2 As shown, the set pulse frequency f=1 / (t1+t2), the duty cycle p=t1 / (t1+t2), it can be seen that the frequency of the actual output complete voltage waveform is only 1 / 2 of the set frequency, and the duty cycle of the positive and negative pulses is both 1 / 2 of the set value.
[0065] The three stages of magnesium alloy micro-arc oxidation under bipolar pulse power supply mode have undergone significant changes. Compared with the unipolar pulse power supply mode, the main performances are:
[0066] 1. During the anodic oxidation stage, under the same voltage and with the extension of time when the voltage remains unchanged, the rate of decrease of the load current further decreases, and the rate of increase of the load equivalent resistance significantly decreases, that is, the film-forming efficiency of the anodic oxidation further decreases. The reason for this phenomenon is that the duty cycle of the actual positive pulse voltage is greatly reduced, resulting in a further decrease in the effective value of the positive voltage.
[0067] 2. In the micro-arc oxidation stage, the arc starting voltage decreases with the increase of the negative pulse voltage, and the value of the arc starting voltage reduction is almost equal to the increase of the negative voltage.
[0068] 3. The process stability of the micro-arc oxidation stage is greatly improved, and the tendency of large arc discharge is greatly reduced, which is manifested as a significant increase in the large arc voltage. Under the same conditions, reducing the duty cycle can slightly reduce the large arc voltage and further reduce the tendency of large arc.
[0069] Compared with the unipolar power supply mode, the bipolar power supply mode introduces negative loading parameters such as negative pulses and negative voltages. The film grows more uniformly and densely, grows faster, and has a lower tendency to form large arcs. It has the following effects on the micro-arc oxidation process:
[0070] 1. Impact on the Great Arc
[0071] As the negative voltage increases, the arc voltage gradually decreases, and the arc tendency increases significantly. The increase in negative voltage leads to a decrease in the arc voltage because the negative voltage also changes the arc starting voltage. The decrease in arc starting voltage is due to the fact that the H2 electrolyzed in the first stage of micro-arc oxidation retained in the conductive channel changes the gas composition in the conductive channel. When the next positive pulse arrives and the positive voltage is loaded, the mixed gas is excited to discharge. The ionization energy of H2 is lower than that of O2, so the arc starting voltage decreases, the arc voltage decreases, and the arc tendency increases.
[0072] 2. Influence on the surface morphology of the film
[0073] Negative voltage has a great influence on the microscopic morphology of the micro-arc oxidation film. As the negative voltage increases, the number of micropores on the film surface increases, and the pore size shows a trend of increasing first and then decreasing. When the negative voltage is low, the film is thinner, the electrolyte temperature is lower than when the negative voltage is high, and the melt cools faster, so there are more crack defects; when the negative voltage is high, the film thickness increases, the melt cooling rate decreases, so there are fewer surface crack defects.
[0074] The micro-arc oxidation process continues, and the molten oxide sprayed from the discharge channel accumulates on the surface to form a film after being cooled and condensed. When a negative pulse is loaded, the negative voltage generates an electron current. The electron current has little effect on the growth of the micro-arc oxidation film, but it has a stronger load capacity than the ion current and is more likely to cause electrical breakdown than the ion current. The electrical breakdown behavior will directly affect the morphology and thickness of the film. At this time, H+ in the solution is prone to reduction reaction, and the ion reaction equation is 2H++2e-→H2↑. The micropores on the surface of the film are channels for the exchange of substances between the electrolyte and the sample, and are also channels for gas escape. When the negative voltage increases, the reduced H2 in the discharge channel increases. When the next positive pulse comes, the substrate is transformed into the anode state. The volume of H2 in the discharge channel increases under the action of the applied positive voltage, which accelerates the rate at which the molten oxide is sprayed to the surface, so the number of micropores increases. The negative voltage affects the microstructure of the micro-arc oxidation film by affecting the size, morphology and density of the plasma discharge.
[0075] 3. Influence on the cross-sectional morphology of the film layer
[0076] As the negative voltage increases, the inner dense layer has many pinhole-like holes, and large pores and cracks gradually appear in the outer loose layer. Due to the insufficient discharge during the film growth process, the bonding between the film and the base metal becomes poor, and the density becomes low. The negative voltage has a reinforcing effect on the next positive pulse. The micro-arc oxidation cathode mainly undergoes a reduction reaction to generate H2. As the negative voltage increases, the more intense the oxidation reaction, the more H2 is generated, and the pressure in the discharge channel increases, thereby accelerating the rate at which the molten oxide is ejected to the surface. If the negative voltage is too high, the gas escapes too fast and the amount increases. The plasma discharge is too intense, and the molten oxide on the surface of the base wraps the gas inside. When cooling and solidifying, traces will be left inside the film, and the density will decrease and the bonding strength will become poor.
[0077] 4. Influence of film thickness
[0078] The thickness of the film increases first and then decreases with the increase of negative voltage. Although negative voltage has a certain effect on promoting the growth of the film, it has a certain degree of tip dissolution effect on the loose layer of the film when it is too large. When a small negative voltage is loaded, a reduction reaction occurs at the anode to generate H2 attached to the surface of the sample. The gas is easily excited under voltage conditions to form gas discharge, generate plasma, and further electron avalanche occurs, resulting in an increase in the tendency of electrical breakdown and an acceleration of the rate of material exchange in the discharge channel. As a result, the thickness of the micro-arc oxidation film increases with the increase of negative voltage. When a large negative voltage is loaded, a reduction reaction occurs. Due to the action of the electric field force, the ions oxidized at the anode in the previous cycle are reintroduced into the discharge channel, resulting in too low a concentration of positive ions near the anode, which is not conducive to the combination of anions and cations, and the thickness of the film decreases.
[0079] In a possible implementation, the preset duration is 10 to 60 minutes.
[0080] In this embodiment, due to the use of an alternating positive and negative pulse preparation method, setting the preparation time at 10 to 60 minutes can effectively play the role of the negative pulse, so that the surface of the film layer obtains a submicron pore structure, reducing the roughness of the micro-arc oxidation film layer, and at the same time, the microporous surface is ablated under the action of the negative pulse, thereby achieving two-dimensional interconnection and adjustable film thickness.
[0081] In a possible implementation, the corrosion-resistant micro-arc oxidation film has a double-layer structure, wherein the inner layer is a dense layer and the outer layer has a two-dimensional interconnected porous structure.
[0082] In this embodiment, by controlling the duty ratio of the positive pulse and the negative pulse, the rate of generation of the oxide film and the ablation rate of the oxide film surface in the micro-arc oxidation process can be adjusted, so that the film thickness is adjustable, and the microporous surface is ablated under the action of the negative pulse, so that the inside of the hole is two-dimensionally connected, generating an oxide film with a dense inner layer and a porous outer layer.
[0083] In a possible implementation, the total thickness of the corrosion-resistant micro-arc oxidation film is 5 to 20 μm, the thickness of the inner layer is 0.5 to 3 μm, and the micropore size of the outer layer is 0.1 to 3 μm.
[0084] In this embodiment, the micropore size of the outer layer of the prepared corrosion-resistant micro-arc oxidation film is 0.1-3 μm, which can reach the submicron level. The pore size of the surface of the oxidation film in this embodiment is small and evenly distributed, which has higher corrosion resistance.
[0085] In a possible implementation, pre-treating the valve metal and / or its alloy substrate includes:
[0086] The valve metal and / or its alloy substrate is ground, polished, laser cleaned or etched to obtain etch pits evenly distributed on the surface of the valve metal and / or its alloy substrate.
[0087] In this embodiment, compared with the grinding and polishing methods in conventional pretreatment, laser cleaning or etching is performed on the substrate surface in this embodiment, which can remove deeper scratches and cracks on the substrate surface, and produce etch pits of uniform size and distribution on the substrate surface, thereby improving the flatness and roughness of the substrate surface, making the substrate surface more suitable for micro-arc oxidation treatment with alternating positive and negative pulses, thereby making the oxide film and the substrate more firmly bonded, and improving the quality of the oxide film layer.
[0088] In a possible implementation, the power of laser cleaning is 5 to 30 W, and the diameter of the etching pit is 5 to 30 μm.
[0089] In this embodiment, Figure 3A The surface morphology of the micro-arc oxidation film prepared by grinding the magnesium alloy substrate (SP) with sandpaper at 34s. Figure 3B The surface morphology of the micro-arc oxidation film prepared by grinding the magnesium alloy substrate (SP) with sandpaper at 36 s. Figure 3C The surface morphology of the micro-arc oxidation film prepared by sandpaper polishing substrate (SP) of magnesium alloy at 41s. Figure 3D The surface morphology of the micro-arc oxidation film prepared by grinding the magnesium alloy substrate (SP) with sandpaper at 51s. Figure 3E The surface morphology of the micro-arc oxidation film was prepared for laser cleaning of the substrate (LC) at 34 s. Figure 3F The surface morphology of the micro-arc oxidation film was prepared for laser cleaning of the substrate (LC) at 36 s. Figure 3G The surface morphology of the micro-arc oxidation film was prepared for laser cleaning of the substrate (LC) at 41 s. Figure 3H The surface morphology of the micro-arc oxidation film was prepared for laser cleaning of the substrate (LC) at 51 s.
[0090] Depend on Figure 3A-3H It can be seen that the LC (20W) sample exhibits a more positive self-corrosion potential and a lower self-corrosion current density compared with the SP sample, indicating that the corrosion resistance of the substrate after laser cleaning has also been improved to a certain extent. This is mainly due to the formation of a relatively uniform oxide film rich in Mg and O on the surface of the substrate during the laser cleaning process of the AZ31 magnesium alloy, which improves its corrosion resistance.
[0091] Figure 4 The potentiodynamic polarization curves of SP sample and LC (10, 15, 20, 25, 30W) sample at different powers in 3.5%wt NaCl solution after micro-arc oxidation. The curves correspond to LC (20W), LC (15W), LC (10W), LC (25W), LC (30W), SP from top to bottom. Figure 4It can be seen that the self-corrosion potential of the micro-arc oxidation film prepared on the substrate after laser cleaning treatment is significantly improved. With the increase of the laser power of the substrate treatment, the corrosion resistance of the micro-arc oxidation film increases first and then decreases. Compared with the micro-arc oxidation films prepared under other power treatments, the LC / MAO (20W) sample has the highest self-corrosion potential and the smallest self-corrosion current density.
[0092] In a possible implementation, the electrolyte includes 2-4 g / L alkaline agent, 10-20 g / L metal salt, 1-2 g / L chelating agent and 0.1-1 g / L complexing agent.
[0093] In this embodiment, the composition and concentration of the electrolyte can be adjusted according to the substrate material and the target performance to prepare an oxide film layer that better meets the requirements.
[0094] In a possible implementation, the alkaline agent is NaOH or KOH, the metal salt is sodium silicate, the chelating agent is citric acid or sodium fluoride, and the complexing agent is one or more of disodium ethylenediaminetetraacetate and sodium phytate.
[0095] In this embodiment, the metal salt is sodium silicate or sodium phosphate, which is used to provide the required metal ions; the chelating agent is citric acid or sodium fluoride, which is used to stabilize the metal ions, enhance the binding force of the micro-arc oxidation film or change the color of the micro-arc oxidation film.
[0096] The following is an example of experimental verification of the method for preparing the corrosion-resistant micro-arc oxidation film provided by the present invention:
[0097] Example 1 takes a 3 mm thick AZ31 magnesium alloy medium and thin plate as the research object, and the specific process steps include:
[0098] (1) Workpiece pretreatment: The AZ31B magnesium alloy substrate was cut into square pieces with a size of 30 mm × 30 mm × 1 mm, and polished with 240#, 360#, 600#, 1000#, and 1500# SiC sandpapers in sequence. The workpieces were polished with a polishing machine, and cleaned with acetone solution and deionized water in an ultrasonic device to remove surface oil and impurities. The workpieces were taken out and dried for later use.
[0099] (2) Laser cleaning: A laser generator (YLP-1-120-50-50-HC-RG) was used to clean the surface of the AZ31B magnesium alloy after pretreatment using a power of 10 W to obtain a laser cleaned sample.
[0100] (3) Preparation of micro-arc oxidation film: The film preparation in this experiment adopts a bipolar pulse micro-arc oxidation power supply (FL7-MAO010X). The power supply works in constant voltage mode. The stainless steel electrolytic cell is used as the negative electrode of the power supply. The substrate after laser cleaning is used as the positive electrode of the power supply, and the positive electrode is completely immersed in the electrolyte. The working process adopts a constant voltage of 380V, the frequency and duty cycle are set to 1500Hz and 35%, the oxidation time is 10min, and the negative pulse (negative voltage 30V). The electrolyte is mainly prepared by adding 10g / L Na2SiO3, 2g / LKOH, and 2g / L NaF to deionized water. The solution is kept at a low temperature by circulating cooling water to obtain a laser-cleaned composite micro-arc oxidation film.
[0101] (4) Sample processing and testing: After preparation, the workpiece is taken out, rinsed with deionized water, dried with a hair dryer, the film thickness is tested with a digital coating thickness gauge, and the corrosion resistance of the workpiece is tested.
[0102] Examples 2 to 5 use AZ31 magnesium alloy medium and thin plates with a thickness of 3 mm as the research object. The specific process steps are different from those of Example 1 only in the laser cleaning power, which is (15, 20, 25, 30 W) respectively. The specific processing steps are shown in Table 1.
[0103] Example 6 provides a submicron ultra-high strength corrosion-resistant magnesium-lithium alloy processing process. This embodiment adopts a certain combination to alternately output positive and negative pulse voltage waveforms, and takes a 1mm thick LZ91 magnesium-lithium alloy sheet as the research object. The specific process steps include:
[0104] (1) Workpiece pretreatment: Cut into individual samples with a size of 30 mm × 20 mm × 1 mm (length × width × thickness). The samples were ground with 400#, 800#, 1000#, 1500#, and 2000# grit silicon carbide papers, and then polished with 2.5μm and 0.5μm polishing agents in turn. During the polishing process, the samples were scrubbed with anhydrous ethanol, taken out and blown dry for later use.
[0105] (2) Experimental equipment and electrolyte configuration: self-developed super-frequency MAO power supply, acrylic cylinder (40 cm × 23 cm × 27 cm) micro-arc oxidation electrolytic cell, stainless steel plate negative electrode, LZ91 magnesium-lithium alloy positive electrode, water cooling system, signal acquisition system. The electrolyte used was a silicate-based electrolyte containing Na2SiO3 (10 g / L), potassium hydroxide (2 g / L) and sodium fluoride (2 g / L), which was stored in an electrolytic cell in an acrylic cylinder. All chemicals (AR) were from Tianjin Yongda Chemical Reagent Co., Ltd. (Tianjin, China).
[0106] (3) Sample preparation: Immerse the treated sample in the prepared electrolyte, connect the stainless steel plate to the negative electrode, connect the LZ91 magnesium alloy to the positive electrode of the power supply, and immerse it completely in the electrolyte. Keep the electrolyte temperature constant during the micro-arc oxidation reaction. Use a heat exchanger to cool the electrolyte by convection heat transfer, and use the acquisition system to collect relevant parameters during the reaction. Start the high-frequency micro-arc oxidation power supply and use the bipolar power supply mode to output positive and negative pulse voltages alternately in a certain combination to perform micro-arc oxidation on the magnesium-lithium alloy. The duty cycle is 30%, the oxidation time is 10 minutes, and the power output frequency is 25kHz.
[0107] (4) Sample processing and testing: After the preparation is completed, the workpiece is taken out, rinsed with deionized water, and blown dry with a hair dryer. After being tested by a film thickness gauge, a micro-arc oxidation film with a film thickness of 19.69 μm is obtained. The workpiece is processed for corrosion resistance testing as shown in Table 2.
[0108] Examples 7 to 10 use LZ91 magnesium-lithium alloy sheets with a thickness of 1 mm as the research object. The specific process steps differ from those of Example 6 only in the use of different ultrasonic pulse frequencies, which are 50 kHz, 75 kHz, 100 kHz, and 150 kHz, respectively. The specific ultrasonic pulse treatment micro-arc oxidation process is shown in Examples 7 to 10 in Table 1.
[0109] Figure 5A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 6, Figure 5B This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Example 6.
[0110] Fig. 6A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 7, Figure 6B This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Example 7.
[0111] Fig. 7A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 8, Figure 7B This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Example 8.
[0112] Fig. 8A is a scanning electron micrograph of the surface of the micro-arc oxidation film of Example 9, Figure 8B This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Example 9.
[0113] Fig.9A is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 10, Fig. 9B This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Example 10.
[0114] Fig.10 Polarization curves of the micro-arc oxidation films of Examples 6 to 10 in 3.5% NaCl solution, wherein the curves correspond to Example 8, Example 7, Example 6, Example 9, Example 10 and the substrate from top to bottom.
[0115] Depend on Figure 5A , B~ Fig.9A It can be seen from Figure B that under the negative pulse condition (negative voltage 50V), with the increase of the ultrasonic frequency, when the ultrasonic frequency reaches 25kHz, 50kHz, 75kHz, 100kHz, and 150kHz, the number of arcing per unit time increases, the arc energy density is small and uniform and stable, and finer micro-arc discharges are generated, resulting in more dense holes on the surface of the film layer, and the hole diameter gradually decreases.
[0116] Depend on Fig.10 It can be seen that under the condition of negative pulse (negative voltage 50V), with the increase of ultrasonic frequency, when it reaches 75kHz, due to the generation of relatively uniform porous submicron holes, the corrosion resistance of the film layer reaches the highest, the self-corrosion current density is reduced by 3 orders of magnitude, and the polarization resistance is increased by 4 to 5 orders of magnitude. However, even with more dense porous submicron holes at 100kHz and 150kHz, its corrosion resistance is still relatively low. This is because the frequency is too large, resulting in the inability of the output pulse energy to penetrate the generated film layer, making the film layer thinner and thus reducing the corrosion resistance.
[0117] Examples 11 to 13 use AZ31 magnesium alloy medium and thin plates with a thickness of 3 mm as the research object. The magnesium alloy composition used in this comparative example is the same as that in Example 1. The specific process treatment is different in that the pulse frequency used is 1500Hz, and no laser is used for cleaning. A 380V constant voltage, a negative duty cycle of 20%, and a negative pulse are introduced using a bipolar power supply mode. The negative voltages are (10V, 30V, 50V) respectively. The specific treatment process is shown in Examples 11 to 13 in Table 1.
[0118] Fig.11 is a scanning electron micrograph of the surface of the micro-arc oxidation film of Example 11, Fig.12 is a scanning electron micrograph of the surface of the micro-arc oxidation film layer of Example 12, Fig.13 FIG. 1 is a scanning electron micrograph of the surface of the micro-arc oxidation film of Example 13. Figures 11 to 13 It can be seen that as the negative pulse voltage increases, the holes gradually become sparse and the hole diameter increases.
[0119] Comparative Examples 1 to 4 use AZ31 magnesium alloy medium and thin plates with a thickness of 3 mm as the research object. The composition of the magnesium alloy used in the comparative examples is the same as that in Example 1. The specific process treatment differs only in that the pulse frequencies used are (500 Hz, 1000 Hz, 1500 Hz, 50 kHz), respectively, and laser cleaning is not used. The specific treatment process is shown in Table 1.
[0120] Fig.14 This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Comparative Example 1. Fig.15 This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Comparative Example 2. Fig.16 This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Comparative Example 3. Fig.17 The scanning electron micrograph of the cross section of the micro-arc oxidation film of Comparative Example 4. Figures 14 to 17 It can be seen that the film thickness of AZ31 magnesium alloy decreases with the increase of frequency.
[0121] The magnesium-lithium alloy composition used in Comparative Examples 5 to 8 is the same as that in Example 6. The specific process treatment differs only in that different degrees of ultra-high frequency are used to change the energy of the pulse frequency, which are (1000 Hz, 50 kHz, 100 kHz, 150 kHz), and a single pulse voltage waveform is used. The remaining steps are the same as in Example 2. The obtained film thicknesses are 23.64 μm, 13.88 μm, and 3.37 μm, respectively. The specific treatment process is shown in Table 1. The obtained ultra-high strength and corrosion-resistant magnesium-lithium alloy is subjected to performance testing, and the results are shown in Table 2.
[0122] Fig.18 This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Comparative Example 5, Fig.19 This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Comparative Example 6, Fig. 20 This is a scanning electron micrograph of the cross section of the micro-arc oxidation film of Comparative Example 7, Fig.21 FIG. 8 is a scanning electron micrograph of a cross section of a micro-arc oxidation film of Comparative Example 8. Figures 18 to 21 It can be seen that the film thickness of LZ91 magnesium-lithium alloy decreases with the increase of frequency.
[0123] Table 1
[0124]
[0125]
[0126] Table 2
[0127]
[0128]
[0129] It should be understood that the order of execution of the steps in the above embodiment does not necessarily mean the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiment of the present invention.
[0130] The following are product embodiments of the present invention. For details not described in detail therein, reference may be made to the corresponding method embodiments described above.
[0131] An embodiment of the present invention provides a metal product, the material of which is valve metal and / or its alloy, and the surface treatment of micro-arc oxidation is performed based on the steps of the method described in the first aspect or any possible implementation of the first aspect.
[0132] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a corrosion-resistant micro-arc oxidation film, characterized in that: include: Pre-treating valve metal and / or its alloy substrate; The pretreated valve metal and / or its alloy substrate is immersed in the electrolyte of a bipolar ultrasonic pulse micro-arc oxidation system, and the micro-arc oxidation parameters are set to a voltage of -50 to 600 V, a power output pulse frequency of 1 kHz to 150 kHz, and a duty cycle of 0.1 to 0.
5. Micro-arc oxidation is performed for a preset time to obtain a metal substrate with a corrosion-resistant micro-arc oxidation film layer.
2. The method for preparing the corrosion-resistant micro-arc oxidation film according to claim 1, characterized in that: The micro-arc oxidation parameters are that the positive pulse voltage and the negative pulse voltage are performed alternately, the forward voltage is 300V to 500V, the negative voltage is -10V to -50V, the pulse frequency is 1kHz to 150kHz, and the duty cycle is 0.3 to 0.
5.
3. The method for preparing the corrosion-resistant micro-arc oxidation film according to claim 2, characterized in that: The preset duration is 10 to 60 minutes.
4. The method for preparing the corrosion-resistant micro-arc oxidation film according to claim 3, characterized in that: The corrosion-resistant micro-arc oxidation film layer has a double-layer structure, the inner layer is a dense layer, and the outer layer has a two-dimensional interconnected porous structure.
5. The method for preparing the corrosion-resistant micro-arc oxidation film according to claim 4, characterized in that: The total thickness of the corrosion-resistant micro-arc oxidation film layer is 5 to 20 μm, the thickness of the inner layer is 0.5 to 3 μm, and the micropore size of the outer layer is 0.1 to 3 μm.
6. The method for preparing the corrosion-resistant micro-arc oxidation film according to claim 1, characterized in that: The pretreatment of the valve metal and / or its alloy substrate comprises: The valve metal and / or its alloy substrate is ground, polished, laser cleaned or etched to obtain etch pits evenly distributed on the surface of the valve metal and / or its alloy substrate.
7. The method for preparing the corrosion-resistant micro-arc oxidation film according to claim 6, characterized in that: The power of laser cleaning is 5 to 30 W, and the diameter of the etching pit is 5 to 30 μm.
8. The method for preparing the corrosion-resistant micro-arc oxidation film according to claim 1, characterized in that: The electrolyte comprises 2-4 g / L of alkaline reagent, 10-20 g / L of metal salt, 1-2 g / L of chelating agent and 0.1-1 g / L of complexing agent.
9. The method for preparing the corrosion-resistant micro-arc oxidation film according to claim 8, characterized in that: The alkaline agent is NaOH or KOH, the metal salt is sodium silicate, the chelating agent is citric acid or sodium fluoride, and the complexing agent is one or more of disodium ethylenediaminetetraacetate and sodium phytate.
10. A metal product, characterized in that: The metal product is made of valve metal and / or its alloy, and is surface treated by micro-arc oxidation based on the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Laser method for improving binding force of ceramic coating and metal matrix
CN109112602A
Preparation method of wear-resistant and corrosion-resistant ceramic layer on surface of magnesium alloy
CN117904685A
Super-audio frequency pulse micro-arc oxidation method and application
CN118028939A
Method for fabricating oxidation film on metallic materials
KR1020160024616A
Cited By
Method for forming protective oxide-ceramic coating on surface of valve metals and alloys
RU2865081C1
Method for forming protective oxide-ceramic coating on surface of valve metals and alloys
RU2865190C1
Method for forming protective oxide-ceramic coating on surface of valve metals and alloys
RU2865192C1